The Working Capital Credit Multiplier - ALMEIDA, HEITOR; CARVALHO, DANIEL; KIM, TAEHYUN (Journal of Finance, 2024)
ABSTRACT We provide novel evidence that funding frictions can limit firms’ short‐term investments in receivables and inventories, reducing their production capacity. We propose a credit multiplier driven by these considerations and empirically isolate its importance by comparing how a similar firm responds to shocks differently when these shocks are initiated in their most profitable quarter (“main quarter”). We implement this test using recurring and unpredictable shocks (e.g., oil shocks) and provide extensive evidence supporting our identification strategy. Our results suggest that funding constraints and credit multiplier effects are significant for smaller firms that heavily rely on financing from suppliers.